Modeling a Logistics Hub Using the Digital Footprint MethodThe Implication for Open Innovation Engineering - Alexey Shmatko; Sergey Barykin; Sergey Sergeev; Anuphat Thirakulwanich (My University, 2021)
Optimizing the cargo flows through the nodes of a digital transport corridor is a crucial problem; solving it allows to introduce modern management methods in logistics. This study examines the optimization of the technology of a distribution center as the base node of a third-party logistics network operator. Our objective consisted in theoretically substantiating the application of mathematical formalisms to describing the passage of stochastic goods flows of a complex structure through a node of a logistics network. To solve the problem, we constructed a mathematical model intended as a decision-making block in the Warehouse Management System software. This paper presents the results of calculations carried out using a computer according to the proposed algorithm. Preliminary results allow to conclude that there is a significant resource for reducing construction and maintenance costs of the distribution center. Quantitatively, the savings will range from 10% to 40%, depending on the terms of delivery of goods and the degree of market uncertainty. An example of a practical calculation using the developed mathematical model is given. The calculations were performed for Huawei, a key global provider of ICT infrastructure and smart terminals. The algorithms were designed to account for uncertainty, which allows to use the results for risk management applications. In practice, this theoretical concept can serve as a basis for digital logistics platforms, increasing the speed of delivery of goods and cargo and the profitability of logistics as a result. The solution to this problem will allow to consider the nodes of logistics networks as smart independent divisions with an information interface for interaction built into a digital logistics platform. The role of these nodes is to make the best decisions in handling cargo flows. As the next stage of research, we plan to develop algorithms for coordinating the information flows reflecting transport activities and forming the material flows entering and leaving the distribution centers.
Keywords: Logistics center; Postponement; Economic and Technological Systems Analysis